Tatuidris kapasi sp. nov.: A New Armadillo Ant from French Guiana (Formicidae: Agroecomyrmecinae). (26th February 2012) - Lacau, Sébastien; Groc, Sarah; Dejean, Alain; Oliveira, Muriel L. de; Delabie, Jacques H. C.
Abstract : Tatuidris kapasisp. nov. (Formicidae: Agroecomyrmecinae), the second known species of "armadillo ant", is described after a remarkable specimen collected in French Guiana. This species can be easily distinguished from Tatuidris tatusia by characters related to the shape of the mesosoma and petiole as well as to the pilosity, the sculpture, and the color.